Effectiveness of Kushal Maa, a group-based mhealth interactive education and social support intervention for maternal and neonatal health outcomes: study protocol for a multisite randomised controlled trial in India - Praveen Kumar; Lakshmi Gopalakrishnan; Nadia Diamond-Smith; Azaz Khan; Abhishek Singh; Rashmi Bagga; Alison M El Ayadi; Anant Bhan; Alka Ahuja; Pushpendra Singh; Mona Duggal; Jasmeet Kaur; et al. (BMJ Open)
Introduction Perinatal care continuity across the full continuum is essential for optimising maternal and infant health; however, a stark gap occurs post partum, with less than one half of Indian mothers receiving postpartum care due to significant logistical and sociocultural barriers, particularly for periurban and rural residents. To overcome these barriers and reduce women’s postpartum isolation, our international team of maternal and infant health clinicians and researchers developed and pilot-tested a culturally-tailored mobile interactive education and support group intervention, Kushal Maa (‘informed-mother’), confirming feasibility and acceptability and preliminary effectiveness. The current study seeks to estimate the effectiveness of the Kushal Maa intervention compared with standard care on maternal and neonatal health-related behaviours and health, characterise the mechanisms of intervention impact and evaluate the cost-effectiveness of the Kushal Maa intervention in improving postpartum maternal and neonatal health compared with the standard of care.Methods and analysis We will conduct a prospective, parallel block-randomised controlled trial with a 1:1 allocation ratio among 2100 pregnant women across three geographically diverse Indian states. Inclusion criteria for women: aged 18+years of age at enrolment, in the last trimester of pregnancy (30–33 weeks of gestation), with any parity, carrying single or multiple gestation (1-2), with knowledge of site-specific local language and had access to a mobile phone. Participants will be block-randomised in groups of 15. Intervention participants will receive 28 tailored education and support sessions weekly via audio/video conference facilitated by trained moderators (four prenatal and 24 weekly postpartum sessions through 6 months) and will be engaged in WhatsApp groups for health education videos and peer discussion via text chat. Control participants receive the standard of care. Data will be collected at four points: 30–33 weeks of pregnancy (enrolment), 6 weeks, 3 months and 6 months postpartum (endline). Investigators, outcome assessors and data analysts will be blinded to group allocation. Primary outcomes will be measured at 6 weeks, 3 months and 6 months post partum and include: postpartum depression (using Edinburgh Postnatal Depression Scale), exclusive breastfeeding and met need for postpartum family planning. Secondary outcomes include other maternal and child health knowledge, outcomes and maternal and newborn healthcare use indicators. We will use intention-to-treat analysis. Mixed-effects models will account for clustering due to the group-oriented delivery of the intervention and repeated measures.Ethics and dissemination This study has been approved by the Health Ministry Screening Committee, Government of India and approved by ethics boards at the Post-Graduate Institute for Medical Education and Research, Chandigarh (Ref:001208, IEC-06/2022–2471), Maharashtra University of Health Sciences (Ref: MUHS/EC/06/2024), Sangath (Ref: AB_2022_81) and the University of California, San Francisco (Ref: 21–35730). All research activities will be performed in accordance with the Declaration of Helsinki. On completion, findings will be disseminated to stakeholders through diverse strategies. Results will be published in academic journals and presented at conferences.Trial registration number ClinicalTrials.gov: NCT05268588 Clinical Trials Registry – India: CTRI/2022/07/043889.